Photon-induced generation and spatial control of extreme pressure at the nanoscale with a gold bowtie nano-antenna platform. Issue 39 (22nd September 2016) - Boutopoulos, Christos; Dagallier, Adrien; Sansone, Maria; Blanchard-Dionne, Andre-Pierre; Lecavalier-Hurtubise, Évelyne; Boulais, Étienne; Meunier, Michel
Abstract : Light-controlled GPa pressure stimulus at the nanoscale with a gold bow-tie nano-antenna platform. Abstract : Precise spatial and temporal control of pressure stimulation at the nanometer scale is essential for the fabrication and manipulation of nano-objects, and for exploring single-molecule behaviour of matter under extreme conditions. However, state-of-the-art nano-mechanical transducers require sophisticated driving hardware and are currently limited to moderate pressure regimes. Here we report a gold plasmonic bowtie (AuBT) nano-antennas array that can generate extreme pressure stimulus of ∼100 GPa in the ps (10 −12 s) time scale with sub-wavelength resolution upon irradiation with ultra-short laser pulses. Our method leverages the non-linear interaction of photons with water molecules to excite a nano-plasma in the plasmon-enhanced near-field and induce extreme thermodynamic states. The proposed method utilizes laser pulses, which in contrast to micro- and nano-mechanical actuators offers simplicity and versatility. We present time-resolved shadowgraphic imaging, electron microscopy and simulation data that suggest that our platform can efficiently create cavitation nano-bubbles and generate intense pressure in specific patterns, which can be controlled by the selective excitation of plasmon modes of distinct polarizations. This novel platform should enable probing non-invasively the mechanical response of cells and single-molecules at time and pressure regimes that are currently difficult to reach with other methods.